2012
DOI: 10.1186/1475-2840-11-136
|View full text |Cite
|
Sign up to set email alerts
|

Association between body size and blood pressure in children from different ethnic origins

Abstract: ObjectiveTo assess associations between body size and blood pressure in children (5-6 years) from different ethnic origins.MethodFive ethnic groups of the ABCD cohort were examined: Dutch (n=1 923), Turkish (n=99), Moroccan (n=187), Black-African (n=67) and Black-Caribbean (n=121). Data on body-mass-index (BMI), waist-to-height ratio (WHtR), fat-mass-index (FMI), and systolic blood pressure (SBP) and diastolic blood pressure (DBP), were collected. Linear regression analysis with restricted cubic splines was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 49 publications
3
9
1
1
Order By: Relevance
“…This is consistent with many previous reports [29][30][31]. However, compared with findings [21,22,[32][33][34][35] in non-Nigerian groups, particularly African-Americans and whites, the present association between BP and body size indicators appears weak. Even so, the present correlation values were higher than those for age (0.05), BMI (0.088) and WC (0.061) reported by Onwubere et al [31] in another Nigerian traditional community of a different ethnicity with a prevalence of hypertension of 46.4% compared with 33.1% found in this study.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with many previous reports [29][30][31]. However, compared with findings [21,22,[32][33][34][35] in non-Nigerian groups, particularly African-Americans and whites, the present association between BP and body size indicators appears weak. Even so, the present correlation values were higher than those for age (0.05), BMI (0.088) and WC (0.061) reported by Onwubere et al [31] in another Nigerian traditional community of a different ethnicity with a prevalence of hypertension of 46.4% compared with 33.1% found in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Since females generally have smaller body size, their blood pressure is lower than that of boys. 14,18 We found no significant difference in SBP between boys and girls (P=0212), but DBP was significantly higher in girls than boys (P=0.009) although the median in the same range due to variations of number of subjects by age group. This discrepancy may be due to greater body mass index (BMI) in girls than boys, increasing with age, leading to higher DBP in girls than in boys.…”
Section: Discussionmentioning
confidence: 51%
“…10,11 Height has an especially important role in determining blood pressure because body size affects blood pressure. [12][13][14] The hydrostatic paradox, first described by Stevin et al, stipulates that fluid pressure generated at the bottom of a tube can be measured from the vertical height of the tube. Fluid can flow from the top to the bottom of the tube when the pressure at the bottom of the tube exceeds the hydrostatic pressure that is defined by its height.…”
Section: To 15 Years According To the Criteria Of The 2004 Fourth Rementioning
confidence: 99%
“…4,5 Body mass index (BMI) is the most frequently used indicator for identifying obesity. 6,7 Although some studies suggested BMI as the strongest predictor of elevated BP, 8,9 the findings are still inconsistent about the best measurement for predicting elevated BP in children. As studies in adults revealed that central obesity is more closely related to cardiovascular disease risk, 10,11 some researchers proposed that the indicators related to abdominal fat, such as waist circumference and waistto-height ratio (WHtR), should be used for identifying elevated BP and other cardiovascular risk in children.…”
Section: Introductionmentioning
confidence: 99%